PENERAPAN METODE TOPSIS PADA SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN VENDOR KLINIK THAMRIN TIGA LIMA MADIUN: APPLICATION OF THE TOPSIS METHOD IN A DECISION SUPPORT SYSTEM FOR VENDOR SELECTION AT THAMRIN TIGA LIMA CLINIC, MADIUN - Sandy Irawan; Retnowati Retnowati (LPPM Universitas Abdurrab, 2026)
In the era of intense business competition in the healthcare sector, selecting reliable vendors is a crucial foundation for the operational efficiency and service quality of the Thamrin Tiga Lima Clinic Madiun. The main challenge faced is the vendor selection process, which is still manual and subjective, potentially leading to operational risks. This research aims to develop, test, and implement an integrated Decision Support System (DSS) to enhance the objectivity, accuracy, and efficiency of the decision-making process. The research adopts the Agile approach and the TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method. TOPSIS was chosen for its ability to handle multi-criteria simultaneously and provide comprehensive ranking results. In this case study, five assessment criteria are used: product quality (C1), price (C2), vendor reputation (C3) and delivery speed (C4). The User Acceptance Test (UAT) results indicate that the system is PASS and ready for implementation, with a user satisfaction level reaching 85.4%. The accuracy of the TOPSIS calculation was also verified at 100%. Based on the case study, the vendor PT. Bina San Prima (V1) ranks first with a preference value of 0,6527. Overall, the developed DSS has proven to be effective in the case study and provides measurable and structured vendor recommendations.